Pulmonary Rehabilitation of a Patient after Lobectomy Secondary to Pulmonary Aspergilloma: A Case Report - Adriana Maria Dsouza; Abeeshna Ashok (Journal of Clinical and Diagnostic Research)
Pulmonary aspergilloma is a mass in the lungs caused by a fungal infection named aspergillosis, which is caused by the fungus Aspergillus. There is a high prevalence of aspergilloma in patients who have previously been affected by pulmonary tuberculosis. The present case report was aimed to describe the radiological features and functional activity limitations of a patient diagnosed with aspergilloma who underwent lobectomy of the superior lobe, middle lobe and superior segment of the lower lobe. A 51-year-old male was admitted with the chief complaint of blood in his sputum, which had increased in volume over the past 10 days, leading to a diagnosis of pulmonary aspergilloma. A Computed Tomography (CT) scan and X-ray confirmed this diagnosis. The patient was referred to the Physiotherapy Department on Postoperative Day one (POD-1). The personalised pulmonary rehabilitation was directed at improving functional mobility and reducing secondary complications of the surgery. The present case report emphasises the importance of tailored pulmonary rehabilitation and its effects on functional independence.